Decoding Morphological Affixation: Unveiling the Top Five Spotify 2020 Lyrics - Halimah, Halimah; Aziz, Muhammad Luthfi (JEDLISH : Journal Of Education and English Language Teaching, 2023)
This study was done due to the importance of morphological awareness for the English learners. By conducting morphological analysis, the learners will have a better understanding about linguistic. They will also be able to increase their vocabulary mastery. As the students have a good vocabulary mastery their other skills of English will increase, too. The intension of this study was to uncover the affixes category and to describe the affixation in the Top Five Track Lyrics of Spotify 2020 Edition as the main data. The qualitative research method was applied by using two instruments to collect the data; observation and documentation. The data gathered then was analyzed in five stages. The result shows that of the five songs been analyzed there were three categories including; Affixes in a Noun, Affixes in an Adjective and Affixes in a Verb found in inflectional affixes, and three categories of derivational affixes; Noun or and Adjectives to Form Adverb, Noun or and Adverb to Form Adjectives and Verb, Adjective, Adverb, or Noun to Form Verb.